Optimizing Early Childhood Motor Development through the Integration of Gymnastics Activities into the Learning Process - Asiah; Pujiyanti, Resti; A'isah, Siti; Jannah, Rihatul (Journal of Educational Technology Innovation and Applications, 2025)
Motor development is a crucial component of early childhood growth that affects children's physical, cognitive, and socio-emotional abilities. As a form of well-planned physical activity, gymnastics can help enhance children's motor skills, particularly gross motor skills. This research focuses on how gymnastics can support the motor development of young children. Gymnastics, when carried out in a fun and active manner, not only trains body strength and coordination but also improves children's focus, discipline, and self-confidence. This study was conducted through participatory observation using a descriptive qualitative approach. The results indicate that improvements in gross motor skills can be achieved through gymnastics, which is performed regularly, systematically, and according to the child’s developmental stage. Therefore, gymnastics should be incorporated into the daily curriculum and integrated with play and learning activities by early childhood educators.